Pemanfaatan Pijat Oksitosin dengan Minyak Sereh pada Ibu Menyusui di Wilayah Kerja Puskesmas Tangkit - Ova Jayanti; Sirly Patriani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Breastfeeding is a way of feeding given directly by mothers to their children, but often breastfeeding mothers lack understanding and lack of information, so often mothers get wrong information about the benefits of exclusive breastfeeding itself, about how to launch breast milk production. The purpose of this community service is to increase the knowledge and skills of mothers in the utilization of oxytocin massage with lemongrass oil in breastfeeding mothers. This community service activity was carried out for 20 breastfeeding mothers in the working area of the Tangkit Health Center, Sungai Gelam Jambi. The method used was face-to-face education and leaflets. The knowledge of breastfeeding mothers was assessed using a questionnaire. Monitoring and evaluation of activities with a one group pretest and post test design approach. The results level of mother's knowledge before being given education were not good with a percentage of >50%. Furthermore, after being given education, the mother's level of knowledge increased with an average percentage of <51.7% to 90.4%, the knowledge component about the citronella oil oxytocin massage technique was still quite low with a percentage of 49.8%. The conclusion is that there is increased knowledge about the benefits of oxytocin massage with lemongrass oil for breastfeeding mothers. It is hoped that it can provide assistance to train mothers' skills in carrying out oxytocin massage with lemongrass oil